PENGGUNANAAN COMPRESSION STOCKING TERHADAP PENCEGAHAN DEEP VENOUS THROMBOSIS (DVT): LITERATUR REVIEW - Najihah Najihah (Universitas Islam Negeri Alauddin Makassar, 2018)
Deep Venous Thrombosis (DVT) is a condition in which a clot forms in deep vein due to inflammation/ venous wall trauma or due to partial venous obstruction. Most DVT comes from lower extremities. Pulmonary embolism is a significant risk for DVT because the release of thrombus then follows the blood flow and is trapped in the pulmonary artery. Compression stocking is one of the compression therapies that helps prevent blood clots that form in the foot by applying pressure varies on each part of the foot. The purpose of this review literature is to determine the effectiveness of using the Compression stocking for prevention of DVT. The process of searching journal articles uses Google Scholar and several databases, namely Cocrane, Proques and Pubmed. Keywords included are